Patient satisfaction after total knee arthroplasty with and without open lateral release in Jordan: a retrospective analysis - Hammad, Zainab; Alghanem, Alaa; Abuthuhayr, Huda; Ebrahim, Fatima; Thaer, Raghad; Talal, Ebtssam; Hamdan, Mohammad; Haddad, Bassem; Alnsour, Omar; Nawaiseh, Mohammad Al (International Journal of Research in Orthopaedics, 2025)
Background: Total knee arthroplasty (TKA) is an effective treatment for advanced knee osteoarthritis, providing substantial pain relief and functional improvement. Patellar maltracking remains a frequent postoperative challenge, and open lateral release (OLR) is often employed to correct abnormal patellar tilt intraoperatively. However, evidence on the impact of OLR on patient satisfaction is limited, particularly in Middle Eastern populations. Methods: We conducted a retrospective analysis of patients who underwent primary TKA with or without OLR at a tertiary hospital in Jordan between 2016 and 2023. Eligible patients had at least six months of postoperative follow-up and were contacted by telephone to complete the Goodman satisfaction scale, which assessed pain relief, function, overall satisfaction, and quality of life (QoL). Mean satisfaction and QoL scores were compared between groups using independent t-tests. Results: A total of 156 patients were included (77 TKA alone; 79 TKA+OLR), with a mean age of 67.7±8.6 years; 80.8% were female. More than 80% of patients in both groups reported being fully or somewhat satisfied with their surgery. Patients undergoing TKA+OLR demonstrated a significantly higher mean satisfaction score compared with TKA alone (85.1 vs. 78.2; p=0.049; 95% CI, 0.04-13.93). Differences in QoL improvement between the groups were not statistically significant (5.09 vs. 4.82; p=0.16). Conclusions: TKA combined with OLR was associated with higher patient satisfaction compared with TKA alone, although QoL improvement was similar between groups. These findings suggest that adjunctive OLR may provide additional benefit in patient-perceived outcomes without compromising overall QoL. Further prospective studies with larger cohorts are warranted to validate these results.